2022
DOI: 10.1177/03635465221109596
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Osteochondral Fragment Fixation Versus Microfracture Even for Small Osteochondral Lesions of the Talus

Abstract: Background: The bone marrow stimulation (BMS) technique is performed for osteochondral lesions of the talus (OLTs) with a lesion size of <100 mm2. The lesion defect is covered with fibrocartilage, and the clinical outcomes deteriorate over time. In contrast, the osteochondral fragment fixation can restore the native articular surface. The difference in clinical outcomes between these procedures is unclear. Purpose: To compare the clinical outcomes of BMS and osteochondral fragment fixation for OLTs and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
7
2
Order By: Relevance
“…Medial lesions that are deeper, cup-shaped, and usually nondisplaced, are thought to have better outcomes than lateral lesions that are shallow and wafer-shaped and often displaced. 5 Unlike our expectations, our data analysis showed no significant difference in the outcome of medial and lateral lesions; all outcome measures (except the Ogilvie-Harris test) were not significantly different between medial and lateral lesions. The same result is reported by Araujo et al 14 Our study has limitations including a small size of the sample population, lack of a comparison group, relatively short follow-up period are limitations of our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Medial lesions that are deeper, cup-shaped, and usually nondisplaced, are thought to have better outcomes than lateral lesions that are shallow and wafer-shaped and often displaced. 5 Unlike our expectations, our data analysis showed no significant difference in the outcome of medial and lateral lesions; all outcome measures (except the Ogilvie-Harris test) were not significantly different between medial and lateral lesions. The same result is reported by Araujo et al 14 Our study has limitations including a small size of the sample population, lack of a comparison group, relatively short follow-up period are limitations of our study.…”
Section: Discussioncontrasting
confidence: 99%
“…(either a single trauma or frequent micro traumas) It has also been estimated that up to 50% of ankle sprains and 73% of ankle fractures can be associated to a pre-existing osteochondral injury. [1][2][3][4][5] Berndt and Harty who determined that osteochondritis dissecans of the talus are the osteochondral fractures due to trauma, have classified OLTs in four different stages (from I to IV), based on the radiologic findings. Loomer and his colleagues added the fifth stage for describing subchondral cysts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports comparing the clinical outcomes of microfracture and osteochondral fragment fixation revealed that osteochondral fragment fixation was superior to microfracture even for small lesion because osteochondral fragment fixation can repair the lesion by coverage with the osteochondral unit while microfracture repairs the lesion by the fibrocartilage. 1,24 There are several limitations to demonstrating the effectiveness of an arthroscopic fixation for medial OLT. The clinical outcomes of this procedure were evaluated by a short-term follow-up period with only 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports comparing the clinical outcomes of microfracture and osteochondral fragment fixation revealed that osteochondral fragment fixation was superior to microfracture even for small lesion because osteochondral fragment fixation can repair the lesion by coverage with the osteochondral unit while microfracture repairs the lesion by the fibrocartilage. 1,24…”
Section: Discussionmentioning
confidence: 99%
“…16,21,32 Furthermore, the influx of joint fluid into the subchondral bone after MF has been reported to induce subchondral bone degeneration. 19,27 As well, multiple perforations in the subchondral bone plate due to bone marrow stimulation have the potential to induce adverse subchondral bone alterations, such as subchondral bone cysts and intralesional osteophytes. 3,11,28 However, the factors causing these alterations have not been elucidated.…”
mentioning
confidence: 99%